Black Soldier Fly Larvae Can Effectively Degrade Oxytetracycline Bacterial Residue by Means of the Gut Bacterial Community - Liu, Cuncheng; Yao, Huaiying; Wang, Cunwen (Frontiers in Microbiology, 2021)
Antibiotic bacterial residue is a unique hazardous waste, and its safe and effective disposal has always been a concern of pharmaceutical enterprises. This report presents the effective treatment of hazardous waste—antibiotic bacterial residue—by black soldier fly larvae (larvae), oxytetracycline bacterial residue (OBR), and soya meal with mass ratios of 0:1 (soya), 1:20 (OBRlow) and 1:2 (OBRhigh), which were used as substrates for larval bioconversion. Degradation of OBR and oxytetracycline, the bacterial community, the incidence of antibiotic resistance genes (ARGs) and the bacterial function in the gut were examined. When the larvae were harvested, 70.8%, 59.3% and 54.5% of the substrates had been consumed for soya, OBRlow and OBRhigh; 65.9% and 63.3% of the oxytetracycline was degraded effectively in OBRlow and OBRhigh, respectively. The larval bacterial communities were affected by OBR, abundant and various ARGs were discovered in the gut, and metabolism was the major predicted function of the gut. These findings show that OBR can be digested and converted by larvae with gut bacteria, and the larvae can be used as a bioremediation tool for the treatment of hazardous waste. Finally, the abundant ARGs in the gut deserve further attention and consideration in environmental health risk assessments.